Mustering the power of ecosystems for adaptation to climate change. Issue 92 (February 2019) - Lavorel, Sandra; Colloff, Matthew J.; Locatelli, Bruno; Gorddard, Russell; Prober, Suzanne M.; Gabillet, Marine; Devaux, Caroline; Laforgue, Denis; Peyrache-Gadeau, Véronique
Highlights: Climate change adaptation in mountain socio-ecosystems builds on historical resilience. The mosaic of grassland types can be managed for bundles of adaptation services. Benefits from adaptation services are accrued along adaptation pathways. Novel governance arrangements build on place attachment and collective institutions. Early stakeholder engagement fosters proactivity against maladaptive trends. Abstract: Mountain social-ecological systems (SES) supply important ecosystem services that are threatened by climate change. In mountain SES there is a paradox between high community capacity to cope with extremes, and governance structures and processes that constrain that capacity from being realised. Climate adaptation that maintains livelihoods and supply of ecosystem services can catalyse this innate adaptive capacity if new adaptive governance arrangements can be created. Using the French Alps as a case study, we outline a participative framework for transformative adaptation that links adaptive capacity and governance to provide social innovation and ecosystem-based adaptation solutions for mountain SES. Grassland management was the main entry point for adaptation: bundles of adaptation services supplied by the landscape mosaic of biodiverse grassland types can maintain agricultural production and tourism and facilitate income diversification. Deliberate management for core adaptation services like resilient fodder production, erosion control, shade or aesthetic value generates co-benefits for future transformation ability. People activate bundles of adaptation services along adaptation pathways and realise benefits via co-production with other forms of capital including traditional knowledge or social networks. Common and distinctive adaptation services in each pathway create options for transformation if barriers from interactions between values and rules across scales can be overcome. For example conserving mown terraces which is a critical adaptation nexus reflects a complex interplay of values, markets and governance instruments from local to European scales. We conclude that increasing stakeholders capacity to mobilise adaptation services is critical for empowering them to implement adaptation to global change.